Diagnostic accuracy of Fatty Liver Index (FLI) for detecting Metabolic Associated Fatty Liver Disease (MAFLD) in adults attending a tertiary care hospital, a cross-sectional study - Roshni Vamja; Yogesh M; Vijay Vala; Arya Ramachandran; Jay Nagda (Clinical Diabetes and Endocrinology)
Abstract Background Metabolic-associated fatty liver disease (MAFLD) is a major public health problem worldwide. This study aimed to determine the prevalence of MAFLD and evaluate the diagnostic accuracy of the Fatty Liver Index (FLI) compared to ultrasonography for detecting fatty liver in adults attending a tertiary care hospital in Gujarat, India. Methods This cross-sectional study included 500 adults visiting the outpatient department between January 2023 and December 2023. MAFLD was diagnosed on ultrasound. FLI was calculated using body mass index, waist circumference, triglycerides, and gamma-glutamyl transpeptidase levels. FLI ≥ 60 indicated fatty liver. Logistic regression analysis identified factors associated with fatty liver. Results MAFLD prevalence was 32.2% on ultrasound. High FLI (≥ 60) was present in 26.2%. Male sex, higher BMI, waist circumference, night shift work, diabetes, and triglycerides were independent predictors of fatty liver. FLI showed excellent diagnostic accuracy with a sensitivity of 96%, specificity of 92.5%, and AUC of 0.92 for detecting fatty liver on ultrasound. Conclusion MAFLD prevalence among adults was high in this hospital-based sample. FLI can serve as an accurate non-invasive tool for identifying individuals with a high probability of MAFLD. These findings emphasize the need for larger population-based studies and the implementation of regular MAFLD screening programs in high-risk groups.